Vechernii Salon . Vechernii Salon . Evening Salon . Вечерний Салон - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Report on Saratov Art Museum and artist Nikolai Gushchin; rip to the manor of Vladimir Nabokov; interview with writer Andrei Bitov about poet Aleksandr Pushkin. Featured in the program: Bitov, Andrei Georgievich (Writer) Репортаж о Саратовском художественном музее и художнике Николае Гущине; путешествие в имение Владимира Набокова; интервью с писателем Андрей Битов говорит об Александре Пушкине. В программе участвуют: Битов, Андрей Георгиевич (Писатель)